A review of parameter settings for galvanic vestibular stimulation in clinical applications - Yishai Valter; Yishai Valter; Linda Vataksi; Aaron R. Allred; Jeffrey R. Hebert; Tad T. Brunyé; Tad T. Brunyé; Torin K. Clark; Jorge Serrador; Abhishek Datta; Abhishek Datta (Frontiers in Human Neuroscience)
Galvanic Vestibular Stimulation (GVS) is a method of manipulating the vestibular system through non-invasive electrical current. Depending on how GVS is applied, it produces specific sensations related to vestibular mediated central pathways. The method has been tested for decades for both medical and non-medical applications and has demonstrated promise in treating a variety of disorders including peripheral vestibular conditions, central vestibular pathology due to neurodegenerative diseases, and post-stroke motor rehabilitation. As GVS continues to grow in popularity and applications, the field lacks clarity on appropriate stimulation parameters, despite their importance for safe and efficacious neuromodulation. This study aims to review the parameters used in various treatment applications while also providing a concise overview of the mechanisms underlying GVS thereby offering essential context and justification for the chosen parameters. We performed a literature search on the PubMed and Embase databases for clinical trials including the term “galvanic vestibular stimulation.” After removing duplicates, secondary analyses, and studies that did not use GVS for therapeutic purposes, we were left with 53 independent studies. We extracted the stimulation parameters used in each study and report them here. The results of this review suggest that while some stimulation parameters are relatively standardized for specific treatment indications, others lack universally accepted guidelines as the field of GVS continues to evolve. Based on our findings, we recommend that future GVS research include at least one sham condition, the use of individualized current intensity, and the comparison of multiple GVS parameters within the same trial.